PENGARUH PENGGUNAAN APLIKASI WATTPAD SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA DALAM MENINGKATKAN MINAT BACA MAHASISWA TINGKAT AWAL - Saputra, Desma Yuliadi; Andriani, Rina (Universitas Sultan Ageng Tirtayasa, 2022)
The aim of this research is to determine the influence of using the Wattpad application as a learning media in enhancing reading interest skills among freshman students. This study employs a quantitative approach, with freshman students as its sample. Data in this research were obtained through the distribution of questionnaires sent randomly to freshman students who are notably in the transitional period from high school to college education. The selection of Wattpad as a media was used as an implementation of learning media to enhance reading interest. Based on the conducted research, there is an increase in reading interest caused by the utilization of online media compared to print media. Additionally, it was found that there is an increase in the vocabulary treasury possessed by students after transitioning to using Wattpad as a media.